Gonadoblastoma: Primary Amenorrhoea with Gonadal Dysgenesis (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A seventeen year old unmarried girl presented with no development of breasts and non establishment of menstruation till then. She was with average height & weight, chromosome analysis was 46XY (Swyer Syndrome). Laparoscopy followed by laparotomy showed irregular surfaced gonads with rudimentary uterus. Gonadectomy done & histopathology revealed features of gonadoblastoma. She had under gone 6 cycles of combination chemotherapy and hormone replacement therapy and showed excellent response. DOI: 10.3329/jbcps.v26i2.4188 J Bangladesh Coll Phys Surg 2008; 26: 97-99